The Development Ideas for Travel Applications Featuring Three Tourism Objects in Indonesia - I Dewa Gde Satrya; Thomas S Kaihatu; Lexi Pranata Budidharmanto (Yayasan Ilomata, 2023)
In recent years, digital transformation has changed the way an organization operates. In the tourism industry, such transformation becomes the necessity as technology keeps developing. Travel can be made easier in some ways, one of which is through the development of travel applications. It is crucial to identify the tourists’ needs and the expectations regarding the user-friendly travel applications. There are in fact a number of applications sprung up in the tourism sector, however, only some of them fulfil the criteria. This study is conducted to develop applications that are considered users-friendly and meet both the needs and the expectations of the tourists. It further investigates what tourists need and expect concerning the related applications. The novelty of this research lies in identifying the expectations and needs of travel apps among millennial by raising case studies in three tourist destinations, namely Borobudur and Dieng, both are in Central Java, and Bayan Village in Lombok. This is a research with a qualitative method. The primary data were obtained through focus group discussions (FGD) and online interviews, whereas the secondary data were generated through literature study. The results indicated that the tourists’ expectations and needs for travel applications are categorized into two groups, the first is the technical aspect and the second is the application content. It was found that tourists require applications with attractive look, supported by clear and updated information. In addition, the applications should be easy to use, help build the enthusiasm to visit, make travel more convenient.